2021
DOI: 10.2147/copd.s326015
|View full text |Cite
|
Sign up to set email alerts
|

MiR-361-5p/abca1 and MiR-196-5p/arhgef12 Axis Involved in γ-Sitosterol Inducing Dual Anti-Proliferative Effects on Bronchial Epithelial Cells of Chronic Obstructive Pulmonary Disease

Abstract: Chronic obstructive pulmonary disease (COPD), a progressive and irreversible respiratory disease, becomes the third leading cause of death and results in enormous economic burden on healthcare costs and productivity loss worldwide by 2020. Thus, it is urgent to develop effective anti-COPD drugs. Materials and Methods: In the present study, two published GEO profiles were used to reanalyze and ascertain the relationships between circulating miRNAs and bronchial epithelial cells (BECs) mRNAs in COPD. The microRN… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 40 publications
0
5
0
Order By: Relevance
“…We further searched the PubMed database (https:// pubmed.ncbi.nlm.nih.gov/) for literature related to miRNAs and COPD airway epithelium to screen for those overlapping with the above 281 miRNAs, excluding nonhuman specimen studies and studies without validation. This identified a total of 19 miRNAs: hsa-miR-130a-3p (24), hsa-miR-21 (25), hsa-miR-223-5p (26), hsa-miR-494-3p ( 27), miR-146a-5p (28), miR-221-3p (29), hsa-miR-92a-3p (29), miR-483-5p (30), hsa-miR-218-5p (31), miR-24-3p (32), miR-218 (33), miR-195 (34), hsa-miR-181c-5p (35), miR-16 (36), miR-222 (36), hsa-miR-29b-3p (37), hsa-miR-200c- 3p (38), hsa-miR-361-5p (39), and miR-146a (40). GO and KEGG enrichment analyses were performed on 7 differentially expressed ferroptosis hub genes.…”
Section: Construction Of the Gene Network And Go/kegg Enrichment Anal...mentioning
confidence: 99%
“…We further searched the PubMed database (https:// pubmed.ncbi.nlm.nih.gov/) for literature related to miRNAs and COPD airway epithelium to screen for those overlapping with the above 281 miRNAs, excluding nonhuman specimen studies and studies without validation. This identified a total of 19 miRNAs: hsa-miR-130a-3p (24), hsa-miR-21 (25), hsa-miR-223-5p (26), hsa-miR-494-3p ( 27), miR-146a-5p (28), miR-221-3p (29), hsa-miR-92a-3p (29), miR-483-5p (30), hsa-miR-218-5p (31), miR-24-3p (32), miR-218 (33), miR-195 (34), hsa-miR-181c-5p (35), miR-16 (36), miR-222 (36), hsa-miR-29b-3p (37), hsa-miR-200c- 3p (38), hsa-miR-361-5p (39), and miR-146a (40). GO and KEGG enrichment analyses were performed on 7 differentially expressed ferroptosis hub genes.…”
Section: Construction Of the Gene Network And Go/kegg Enrichment Anal...mentioning
confidence: 99%
“…2. The PSS reported were sitosterol (SITO) in five studies (37)(38)(39)(40)(41)(42) , Antcin-A (ATA) (43,44) and stigmasterol (STIG) (45,46) in two studies each and ergosterol (ERGO) (47) , and campesterol (CAMP) (45) in one each. Four studies completed experiments in breast cancer cell lines (38,39,43,48) , two in models of coronary obstructive pulmonary disease (42,47) , one in prostate cancer cell lines (40) , one in neural stem cells (37) , one in human aortic endothelial cells (41) , one in BALB/c-nude mice (38) , one was in guinea pigs (46) and one in silico (45) .…”
Section: Resultsmentioning
confidence: 99%
“…Similarly in HAEC, signalling pathway analysis indicated that SITO treatment enriched for AKT signalling, forkhead box O transcription factors and cell cycle signalling ( 37 ) . Contrary to this, the bronchial epithelial airway cell line model of chronic obstructive pulmonary disease (BEAS-2B) responded to very low concentrations of SITO (60 nM for 24 h) by induction of miR-196-5p and suppression miR-361-5p, leading to inhibition of mTOR signalling and reduced proliferation ( 42 ) .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations